A giant recurrent myxoid liposarcoma of the retroperitoneal and peritoneal cavity - Snarska, Jadwiga; Suszkiewicz, Rafał; Iwanowicz, Katarzyna; Biernacki, Maciej; Michalak, Maciej; Biedziuk, Bartłomiej; Bogucki, Paweł; Sulik, Marian (Contemporary Oncology/Współczesna Onkologia, 2009)
Liposarcomas belong to the very seldom occurring group of malignant tumours of the retroperitoneal cavity. Usually they develop in adult patients. The pathogenetic factors are still unknown. The molecular surveys prove the specific translocation in the range of chromosomes in the case of myxoid liposarcoma. Growth of this type of tumour is slow and spreading. They can achieve very large sizes. The basic diagnostic examinations are ultra-sonography and tomography of the abdominal cavity. The basic treatment of liposarcoma is surgery, if possible radical resection of the whole tumour. In this case, the tumour removed by our medical group weighed 24.45 kg in seven parts. It occupied not only the retroperitoneal cavity but also the whole abdominal cavity. Despite the removal of such a gigantic tumour, this kind of intervention is hard to consider as very radical. Literature data indicate that one of the essential risk factors of tumour recurrence is the size of the tumour. We would like to present the described case with regard to the rarity of occurrence: the enormous size, asymptomatic course of the disease, and recurrence 20 years after primary surgical treat-ment.